Regulation of Entrepreneurial Structure Development Based on E-Commerce Technologies - KNIAZ SVIATOSLAV; FALDYNA VOLODYMYR; DANKO TETYANA (Communications of International Proceedings, 2021)
The regulation of development of business structure on the basis of e-commerce technologies is considered in the given material. It is proved that the model of regulating the development of business structure based on e-commerce technologies is a system. The components of this regulation model are highlighted and the relationships between them are clarified. The system of regulating the development of business structure based on e-commerce technologies from the standpoint of cyclical theory of fractals is presented, and this system is reflected as a decomposition structure, on the example of the hierarchy of goals.
Keywords: Regulation; Development; Business Structures; E-Commerce Technologies.